STAGES OF DEVELOPMENT OF THE MODERN UZBEK LITERARY LANGUAGE - Yuldasheva Dilnoza Bekmurodovna; Vasiyev Navruz Olimjon o’g’li (Web of Journals Publishing, 2024)
This article explores the stages of development of the modern Uzbek literary language, tracing its historical evolution from ancient Turkic roots to its present form. The study highlights significant periods, including the influence of Chagatai Turkic, the impact of cultural and political shifts during the Soviet era, and the role of independence in shaping contemporary Uzbek. Key linguistic and literary milestones are analyzed, illustrating how historical events and social changes have influenced vocabulary, grammar, and literary style. The article also examines the contributions of notable writers and poets in standardizing and enriching the language. Through this comprehensive overview, the research underscores the dynamic nature of the Uzbek literary language and its role in preserving cultural identity.
Keywords: Uzbek literary language, language development, Chagatai Turkic, Soviet influence, independence, linguistic evolution, cultural identity, literary milestones, modern Uzbek.